2000
DOI: 10.1161/01.str.31.8.1945
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Injury in Spinal Cord Ischemia

Abstract: Background and Purpose-Spinal cord ischemia is a serious complication of surgery of the aorta. NMDA receptor activation secondary to ischemia-induced release of glutamate is a major mechanism of neuronal death in gray matter. White matter injury after ischemia results in long-tract dysfunction and disability. The AMPA/kainate receptor mechanism has recently been implicated in white matter injury. Methods-We studied the effects of AMPA/kainate receptor blockade on ischemic white matter injury in a rat model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(15 citation statements)
references
References 51 publications
1
13
0
1
Order By: Relevance
“…The severity of white matter damage, assessed by MBP immunostaining, in a rat model of perinatal hypoxia-ischemia was reduced by systemic administration of NBQX (Follett et al, 2000). This agent also attenuated the extent of axonal damage, assessed by neurofilament immunostaining, and improved locomotor function in a rat model of spinal cord ischemia (Kanellopoulos et al, 2000). After traumatic injury to the spinal cord of rats, NBQX not only improved the survival of oligodendrocytes but also reduced axonal injury and attenuated impairment of locomotor function (Rosenberg et al, 1999;Wrathall et al, 1994Wrathall et al, , 1996Wrathall et al, , 1997.…”
Section: Glutamate Receptor Antagonistsmentioning
confidence: 92%
“…The severity of white matter damage, assessed by MBP immunostaining, in a rat model of perinatal hypoxia-ischemia was reduced by systemic administration of NBQX (Follett et al, 2000). This agent also attenuated the extent of axonal damage, assessed by neurofilament immunostaining, and improved locomotor function in a rat model of spinal cord ischemia (Kanellopoulos et al, 2000). After traumatic injury to the spinal cord of rats, NBQX not only improved the survival of oligodendrocytes but also reduced axonal injury and attenuated impairment of locomotor function (Rosenberg et al, 1999;Wrathall et al, 1994Wrathall et al, , 1996Wrathall et al, , 1997.…”
Section: Glutamate Receptor Antagonistsmentioning
confidence: 92%
“…23 It has been shown that both gray and white matter were damaged after spinal cord ischemia in rats, and the severity of white matter injury was correlated with the degree of gray matter injury. 24,25 Kannellopoulos et al 26 demonstrated widespread and prominent vacuolation in white matter 2 days after the experimental spinal cord ischemia. The mechanism of injury induced by reoxygenation in axons has been proposed to be the failure of respiration due to severe mitochondrial Ca 2 þ overload.…”
Section: Discussionmentioning
confidence: 99%
“…OLG death in these disorders results, in part, from excitotoxicity involving AMPA receptor (McDonald et al, 1998;Smith et al, 2000;Miller and Mi, 2007). AMPA receptor antagonism is effective in salvaging white matter after traumatic or ischemic SCI (Wrathall et al, 1994;Kanellopoulos et al, 2000).…”
Section: Introductionmentioning
confidence: 99%